Pengaplikasian Metode Penginderaan jauh dan Pendekatan Geologi Sederhana dalam Kajian Masalah Penurunan Tanah di Wilayah Pesisir Semarang dan Demak: Studi Komparasi antara Asumsi Umum dan Alternatif - Sinatrya Diko Prayudi; Hayat Safi’i; Najib Najib (Prosiding TAU SNARS-TEK Seminar Nasional Rekayasa dan Teknologi, 2019)
The land subsidence occurring in the coastal of Semarang City and Demak Regency is one of the geological disaster issues that is quite interesting to discuss. With the subsidence rate ranging from 10 cm/year and the proof on the surface can be observed through the naked-eye, causing the local government to look at this problem seriously enough to know the main problems. Referring to some research, a strong suspicion arises as an influencing factor, namely over-exploitation of groundwater that high enough to overdo the coastal area which causes the aquifer to be depleted underneath and triggers aquifer compaction, making the layer become unstable and triggers land subsidence at surface. The assumptions made in Semarang City are not in line with what happened in the coastal area of Demak Regency, because the area does not over-exploited, but its territory now submerged by seawater. In research carried-out using a methodology that includes literature study, analysis of remote sensing imagery data, and regional geological approaches. Several literature studies found indicate that there are other factors that trigger land subsidence with addition to groundwater problem, namely the existence of subsurface geological structures where the appearance on surface is not visible, with intersecting directions. The distribution of areas subject to the structure based on results of the remote sensing analysis includes areas where intensive land subsidence occurred on one side and areas not affected on the other. The movement of these subsurface structures is thought to trigger an increase or decrease in subsurface rock blocks and cause quaternary alluvium deposits above become unstable based on the geological approach. Some of these conditions triggered the emergence of new assumptions besides factors from groundwater extraction in the study area.